Effect of probiotic on the fecal slgA level in preterm infants (A randomized double-blind placebo control study) - Lucia P Retnaningtyas; Subijanto M Sudarmo; Ariyanto Harsono; Sylviati M Damanik (Indonesian Pediatric Society Publishing House, 2008)
Background Secretory immunoglobulin A (slgA) plays an important role in the defense of gastrointestinal tract. Preterm infants that developed abnormal pattern of bowel colonization may benefit from strategy to support maturation of humoral im- munity and endogenous production of slgA by early colonization with probiotic. Objective To evaluate the effect of pro biotic on the fecal slgA level in newborn preterm infants. Methods A randomized control study of newborn pre term infants was conducted in NICU Dr Soetomo Hospital, Surabaya in November-December 2007. Pro biotic group was given multi- strain pro biotic containing 107 cfu of Lactobacillus acidophil us, Bifidobacterium longum, and Streptococcus faecium once daily for 14 days from second day of life. Fecal slgA was determined by ELISA before and after intervention. Subjects who got respiratory distress syndrome (RDS) or sepsis during the study was dropped out. Statistical analysis used in this study were chi-square, inde- pendent sample t-test, Mann-Whitney, Wilcoxon Signed-Ranks test, and multivariate analysis of variance (a=O.OS). Results Forty seven neonates were enrolled, seven of them were dropped out. Forty analyzed neonates were divided in probiotic (n = 20) and placebo group (n = 20). The basic characteristics of two groups were similar. At first examination, median of fecal slgA level did not differ significantly between groups (P=0.512), 0.164 and 0.174mg/g feces in probiotic and placebo group respectively. There was higher increment of fecal slgA level in pro biotic than placebo group post treatment(1.735 versus 1.449 mg/g feces, P=0.003). Conclusion Preterm infants may benefit from probiotic because of the clear tendency to increase fecal slgA secretion